O PROCESSO DE ESCOLARIZAÇÃO DO ESTUDANTE COM AUTISMO: CAMINHOS ALTERNATIVOS E PRÁTICAS SIGNIFICATIVAS NO CONTEXTO ESCOLAR - Dalvi, Daiana Alves de Jesus (2021)
Understanding the importance of the learning process of students that struggle with autism and the pedagogical practices that are relevant in an academic context in order to direct the view for possibilities that establish on a daily basis at the schools. By this mean, making use of other ways that meet the singularity that is being a human, making possible the student’s participation in the teaching and learning process that is nonstop within the scope of pedagogical practices. The following study aims to understand how does the specifics of the learning process of students that struggle with autism work, since an offer of intervention elaborated by a researcher, joined by specialized teachers that perform in common teaching classrooms, bringing forward their daily insights on the classrooms and the experience with remote learning, as well as the results of collaboration with the specialized teachers making a work in progress with students that have autism. The focus was on the visual resources in order to evoke the interest of the students to accomplish the planned activities. At first, it was initiated the activities at the time and space of the school environment. Thereby, as the project continued, it was necessary to get in a second school space and experience other stories with other participants, in a historical context that is the pandemic. The work in progress is a theoretical reference and methodologically in the Cultural-Historical approach of human development, elaborated by Vigotski (2000, 2009, 2011, 2014, 2018, 2020) and collaborates, for understanding that we construct new meanings after new experiences, and that the intentionally thought practices are in favor of the children and teenager’s development. Considering the analysis given by the research the conclusion was that it’s necessary to acknowledge the singularity of students that struggle with autism without singling them out of the school experiences that are given in the historically cultural and social environment. By any means, it’s understood through experiences with Davi and Anne, two of the research’s participants, that it is possible to plan thought classes to understand everyone, without limiting them to the space of the classroom. The study also directed us to use alternative ways and suitable thoughts to attend the student’s educational needs that participate in this research, indicating that the collaboration involves partnerships between the professionals that serve the students, defragmenting the pedagogical action, reassuring that the collaboration involves study, afterthought, connection and intentional planning to attend the students pedagogically that struggle with autism.